GURU PROFESIONAL (Sebuah Karakteristik Guru Ideal Dalam Pendidikan Islam) - Muhlison, Muhlison (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2014)
Profession of teacher in Islam education will very related and determine his existence as figure becoming peer, especially related to applying of values of Islam teaching at school or society. Especial and dignity of teacher non lay in his teacher profession, but lay in glory duty which shouldered Therefore various interest have to be owned by a teacher in order to improving his professional as somebody to a lot of positioned as icon from various value and teaching in so many life sector ; family, school, and also society . In contact with activity and result of learning student, interest of playing important role teacher. Process learn to teach and result of learning all student not only determined by school, pattern, structure and fill its curriculum, however most determined by teacher interest.